Upaya Meningkatkan Mandiri Belajar Siswa Melalui Pembelajaran Metode Kooperatif Learning pada Pelajaran Pendidikan Agama Katolik Bagi Siswa Kelas IX SMPN 2 Banyuke Hulu - Tulus Tulus; Brigida Intan Printina; Vinsensius Kriswidiatma Tjahja (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research desires to know the Cooperative learning model in general in an effort to improve the independent learning of students in the classroom. Data collection and literature study using Classroom Action Research through data from cycle 1 and comparison results from cycle II. Cooperative is willing to help or be cooperative, in cooperative activities always require a group. While the Group is a group of several people who have the same goals desires and expectations. Meanwhile, group learning is a process of planned and directed learning activities involving more than one person so that where between one person and another complement each other. In learning the Cooperative method in this Classroom action research aims to increase independent learning, which means that if students are able to learn independently, it can describe that increased learning in Catholic religious education. The problem in this study is that the application of cooperative learning methods has not been applied optimally in learning. Research based on the problem, (a) How is the implementation of cooperative learning methods in Catholic Religious Education lessons to improve independent learning in class IX students of SMPN 2 Banyuke Hulu. (b) How is the improvement of student learning outcomes after applying Cooperative Method learning in Catholic religious education subjects. The objectives of this action research are; (a) to find out the Implementation of Cooperative Method Learning in Catholic religious education. (b) to determine the increase in student learning outcomes after the application of Cooperative Method Learning in Catholic religious education subjects for class IX students of SMPN 2 Banyuke Hulu.